Motion - Computerized Tomographic Colography is a Better Method for Screening for Polyps: Arguments Against the Motion - Jerome B Simon (Canadian Journal of Gastroenterology)
Computerized tomographic (CT) colography is an exciting technique whereby images of the colonic wall and lumen can be obtained without colonoscopy. It is not as good as conventional colonoscopy, however, because of both inherent and performance limitations. Among the former is the inability to visualize subtle mucosal lesions, such as alterations in colour or pliability. More importantly, CT colography is strictly a diagnostic technique, and does not allow biopsy or removal of polyps. The vigorous bowel preparation required for this procedure can be very unpleasant for the patient, and includes purgatives followed by distension of the colon with air. Unlike with colonoscopy, adherent stool can be difficult to distinguish radiologically from polyps or cancers; as a result, many patients require colonoscopy anyway. The major performance limitations of CT colography are poor sensitivity and specificity compared with conventional colonoscopy. Rectal lesions, flat adenomas and diminutive adenomas are especially difficult to detect, and false-positive results are also common. In addition, the procedure is expensive and less cost effective than colonoscopy. CT colography takes relatively little patient time, but a substantial amount of time is needed for the radiologist to interpret the images. Interobserver variability is high. For all of these reasons, CT colography cannot be recommended as a screening test for colorectal neoplasia.